The Influence of Transformational Leadership and Emotional Intelligence of Madrasah Principals on Teacher Performance at MTSN 7 Jakarta - Susianingsih Susianingsih; Yuni Pratikno; Jamal Hanaffy (Dinasti Publisher, 2026)
Teacher performance is a strategic factor in determining the quality of the learning process and the achievement of educational goals, especially at State Islamic Junior High School (MTsN) 7 Jakarta. Improvement in teacher performance is influenced by various internal factors, including transformational leadership and emotional intelligence. This study aims to analyze the influence of transformational leadership on teacher performance, the influence of emotional intelligence on teacher performance, and the influence of transformational leadership and emotional intelligence simultaneously on teacher performance at MTsN 7 Jakarta. This study uses a quantitative approach with a survey method that emphasizes the collection and processing of data in numerical form so that the results of the analysis can be interpreted objectively and measurably. To enrich the understanding of the variables studied, this study is also supported by qualitative data in the form of verbal statements in questionnaires and open comments from respondents. The study population was 58 teachers, with a sampling technique using total sampling, so that the entire population was used as respondents. Hypothesis testing was conducted using multiple linear regression analysis with the help of SPSS software version 29. The results showed that partially transformational leadership and emotional intelligence have a positive and significant effect on teacher performance. Simultaneously, both variables also showed a significant effect on teacher performance. The coefficient of determination (R Square) value of 0.495 indicates that 49.5% of the variation in teacher performance can be explained by transformational leadership and emotional intelligence, while the remaining 50.5% is influenced by other factors outside the research model. This finding confirms that strengthening the transformational leadership style and developing teachers' emotional intelligence are important factors in improving teacher performance at MTsN 7 Jakarta